Development of the hybrid information and analytical system for management reporting in the organization - Dudchenko Anastasiia; Karaseva Tatiana (ITM Web of Conferences)
There is an increasing emphasis on improving the efficiency of management reporting systems due to the development of information technologies. This paper describes the experience of implementing a hybrid reporting management system. The paper substantiates the choice of system components and presents a model of the proposed solution.